THE ROLE OF SURVIVIN AND RAF-1 KINASE AGAINST ENHANCEMENT OF PANCREATIC BETA-CELL APOPTOSIS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Decroli, Eva; Manaf, Asman; Syahbuddin, Syafril; Waspadji, Sarwono; Dillasamola, Dwisari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to reveal differences in levels of survivin and Raf-1 kinase in prediabetes, controlled Type 2 diabetes mellitus (T2DM), uncontrolled T2DM, and their relationship with hemoglobin A1c (HbA1c) levels and serum triglyceride levels. Methods: This study was an observational study with a cross-sectional design. The study involved 60 people with T2DM who visited the endocrine and metabolic clinic and 30 prediabetes patients. The variables were survivin levels and Raf-1 kinase enzymes that examined using enzyme-linked immunosorbent assay techniques. HbA1c values are measured by high-performance liquid chromatography and triglyceride levels measured by enzymatic method. Results: Average levels of Raf-1 kinase were significantly higher in the prediabetes group, controlled T2DM, and uncontrolled T2DM (11.6±1.4 pg mL, 9.9±1.1 pg/mL, and 9.1±1.5 pg/mL). Survivin was significantly higher in the prediabetes group, controlled T2DM, and uncontrolled T2DM (5.4±0.4 pg mL, 5.0±0.2 pg/mL, and 4.7±0.1 pg/mL). There was no correlation between HbA1c with Raf-1 kinase levels (R=−0.215, p=0.250), but there was a correlation between HbA1c with serum survivin levels (R=−0.6, *p<0.05). There was a correlation between the levels of triglycerides with survivin but not with Raf-1 kinase (R=−0.267, *p=0.039). Conclusion: Survivin and Raf-1 kinase levels are lower in uncontrolled T2DM. This explained the role of survivin and Raf-1 kinase against enhancement of pancreatic beta-cell apoptosis in patients with T2DM.